Genome-wide identification, expression and functional analysis of glutathione s-transferase family members in Quercus dentata under heavy metal stresses - Sha, Jingjing; Wu, Xiangyue; Shen, Ao; Pang, Xin; Wang, Wenbo; Leng, Pingsheng; Hu, Zenghui; Zhao, Yazhou; He, Xiangfeng (Frontiers in Plant Science, 2025)
Glutathione S-transferases (GSTs), a superfamily of multifunctional enzymes, are involved in plant growth, development, and response to biotic and abiotic stresses. In this study, 86 members of the GST family, denoted QdGST, were identified in the Quercus dentata genome and found to be distributed among six of the GST classes, with the majority in the tau class, followed by the lambda and phi classes. This uneven distribution of QdGST genes was observed across 11 chromosomes. Thirty-one tandem and seven segmental duplication events were found to have contributed to the expansion of the QdGST family. Moreover, a total of 29 categories of cis-acting elements were identified in the promoters of the QdGST genes, most of which were involved in defense and stress responses. RNA sequencing analysis revealed that most QdGST genes displayed tissue-specific expression patterns, and that cadmium or lead treatment induced the expression of 31 of them, most of which belonged to the tau class. Quantitative real-time PCR analysis confirmed the expression of cadmium- and lead-induced QdGST genes, with QdGSTU20 and QdGSTU36 in particular showing strong upregulation. QdGSTU36 also enhanced yeast growth under cadmium and lead stresses when expressed in yeast. These findings lay a crucial foundation for further work to clarify the biological functions of QdGST genes associated with heavy metal tolerance in Q. dentata.